English Students’ Performance on Part A of Listening Comprehension in TOEFL Prediction at Syiah Kuala University - Ashra Winda Berliyani; Nira Erdiana (Universitas Syiah Kuala, 2017)
This study was aimed to figure out how is the performance on Part A of listening comprehension in TOEFL prediction faced by English students. This performance is based on the skills performance consists in Part A. This study took place in Syiah Kuala University. The sample of this study was limited to 15 English students batch 2010 to batch 2014 which was taken by using purposive sampling technique. Listening section on Part A was given to the students who had been selected as the sample of this study when they took TOEFL in Language Center of Syiah Kuala University. The skills found in Part A of listening TOEFL prediction are 7 skills. The students here took TOEFL as the requirement for applying seminar proposal and thesis examination. The result of part A showed that their performance on Part A in these 7 skills was low in average. It could be seen from the result using document analysis which showed that these 15 students got the true answer in each question is under 50 %. Therefore, it showed that their performance on Part A of TOEFL prediction was failed in average. From this research, it can be concluded that the most problematic skill found is suggestion 18,89 % and the most mastered skill is idiom 46,67 %. It means that they were failed to get the score expected on Part A in each skill and got less of true answer in every skill tested. In conclusion, the performance of English students on Part A is failed in general.